KSA Landing at University: Implementación e integración - Espinel González, María Almudena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study is a proposal for the implementation of a competency-based teaching model at university, taking advantage of the experience of having integrated a new transversal subject in the pilot course called KSA (Knowledge, Skills and Attitudes) imposed by the European Aviation Safety Agency (EASA) for all Aviation Schools of the member States, which forced the change of the study plans and learning objectives for the pilot course, specially, the university degree.